Shaquille O$1 (BNeal :s Shaq attack - Cox, Ted. (Chicago : Childrens Press, 1993)
A biography of the basketball player who, in only his second year as a professional, is being compared to the game$1 (Bs greatest players.s
"Childrens Press reinforced binding"--P. [4] of cover.
Keywords: O$1 (BNeal, Shaquilles -- Juvenile literature; O$1 (BNeal, Shaquille.s; Basketball players -- United States -- Biography -- Juvenile literature; Basketball players; African Americans -- Biography